Automated Vehicle Access Control System Utilizing Computer Vision-Based License Plate Recognition - Juliano, Joseph J.; Armada, Marc Kiane A.; Cosadio Jr., Angelito N.; Portugues, Frnacis F.; Reyes, Rickron E. (Future Science / FSH-PH Publications, 2025)
The evaluation of the Automated Vehicle Access Control System utilizing Computer Vision-Based License Plate Recognition demonstrated excellent performance based on ISO/IEC 25010:2011 quality metrics, achieving a Grand Mean of 3.31, categorized as